Control Theory Tutorial: Basic Concepts Illustrated by Software Examples - Frank, Steven A. (SpringerBriefs in Applied Sciences and Technology, 2018)
Control Theory; Engineering Design Tradeoffs; Robust Control; Feedback Control Systems; Wolfram Mathematica Software; Optimal Control